Infantile Hyperchylomicronemia Due to A Novel GPIHBP1 Disease-Causing Variant Presenting with Milky Blood: A Rare Case Report - Iman Marzouq; Basant Elbanna; Sabine Schröder; Kornelia Tripolszki; Aida M. Bertoli-Avella; Aml Mahfouz (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Familial hyperchylomicronemia is a very rare autosomal recessive disorder and the most severe type of pediatric hyperlipidemia. The purpose of this case report is to enhance clinician's insight on the diagnosis and management plan in the case of infantile hyperchylomicronemia presenting with milky blood. Case: We reported a 2-month-old infant with familial chylomicronemia syndrome. The patient was ‘accidentally’ diagnosed by the observation of milky blood. Exome sequencing revealed a homozygous likely pathogenic GPIHBP1 variant (NM_178172.5:c.193T>C p.(Cys65Arg)) confirming the diagnosis. He was treated with low-fat diet, a formula rich in medium-chain triglycerides and fenofibrates. After 4 days, his serum triglycerides decreased markedly. Fenofibrates were stopped at the age of one year and his serum triglycerides were maintained at low level with dietary measures. No complications occurred during two years follow-up period. Discussion: Clinical manifestations of familial chylomicronemia syndrome start in early life with a very high level of hypertriglyceridemia and with monogenetic etiology, in contrast to multifactorial chylomicronemia syndrome that starts in adulthood, with proposed polygenic etiology. The main treatment of familial chylomicronemia syndrome is dietary fat restriction to less than 15% of the total caloric intake and medium-chain triglycerides which can bypass the chylomicron pathway of fat metabolism. Conclusion: The main challenge in this case was the early diagnosis to protect the patient against serious complications. The mainstay of therapy is low-fat diet and medium-chain triglycerides. This case illustrates the relevance of establishing a timely genetic diagnosis and treatment.